1913
DOI: 10.5962/bhl.title.13015
|View full text |Cite
|
Sign up to set email alerts
|

Parasitische und kommensalistische Mollusken aus Holothurien / von M.M. Schepman und H.F. Nierstrasz.

Abstract: Megadenus voeltzkowi n. sp. (Fig. 1 u. 2.) Schale eiförmig, mit plötzlich verschmälerter Spitze; Windungen etwa 6, von welchen ungefähr-Ij eine stielförmige Spitze bilden; die beiden folgenden Windungen sind schmal, leicht gewölbt; die \nerte ist schon beträchthch breiter und stark konvex, durch eine deutliche Naht von der folgenden getrennt; die fünfte und sechste bilden fast die ganze Schale, sie sind sehr konvex, mit noch deutücherer Naht. Die ganze Schale ist sehr durchscheinend, schwach weißlich, sehr gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Although sometimes erroneously construed as seminal receptacles or vesiculae seminales (Schepman and Nierstrasz 1913;Spärck 1931), these structures are actually true spermatophores and occur in representatives of all four genera as they do in the present species, while they are absent from all other bivalves. All galeommatoideans are brooders which require that sperm in one way or another get access to the ctenidial or siphonal brood chamber.…”
Section: Reproductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Although sometimes erroneously construed as seminal receptacles or vesiculae seminales (Schepman and Nierstrasz 1913;Spärck 1931), these structures are actually true spermatophores and occur in representatives of all four genera as they do in the present species, while they are absent from all other bivalves. All galeommatoideans are brooders which require that sperm in one way or another get access to the ctenidial or siphonal brood chamber.…”
Section: Reproductionmentioning
confidence: 77%
“…Moreover, the surface of the mantle and most parts of the foot are provided with a very delicate cuticle, a structure not compatible with an absorptive surface. Malard (1903) suspected Devonia perrieri (Malard, 1903) pulled host tissue into the byssus gland for ingestion, but this was doubted by Schepman and Nierstrasz (1913) and Ohshima (1931). Voeltzkow (1890) also considered E. mirabilis to be a parasite, but in spite of this observed that it fed on organic matter, such as diatoms engulfed by its host.…”
Section: The Footmentioning
confidence: 99%
“…Comparison of the main character states separating the species of Megadenus. The information provided is based on literature (Schepman and Nierstrasz 1913;Humphreys and Lützen 1972;Bouchet and Lützen 1980;Takano et al 2017). For M. holothuricola and M. smithi sp.…”
Section: Megadenus Holothuricola Rosén 1910mentioning
confidence: 99%
“…There is almost no information on the relations between Holothuria fuscocinena and Entovalva major which is said to supposedly live in the holothuroid cloaca (Bruun 1938). Entovalva mirabilis and Cycladoconcha amboinensis inhabit small pouches dug into the digestive wall of synaptid holothuroids (respectively Voeltzkow 1890, Schepman & Nierstrasz 1914Sparck 1931). These 3 species are presumably typical suspension feeders.…”
Section: Agents: Mollusca Bivalviamentioning
confidence: 99%